The Influence Of Overconfidence, Risk Tolerance, And Herding Behavior On Cryptocurrency Investment Decisions Among Students In Surabaya - Hermawati, Nelsha Fariska (JMM17 : Jurnal Ilmu ekonomi dan manajemen, 2025)
The phenomenon of increasing interest in digital asset investment among university students is often not accompanied by adequate financial literacy, leading to investments being made based on trends or social influence without careful risk consideration. In light of this, the present study aims to analyze the influence of overconfidence, risk tolerance, and herding behavior on cryptocurrency investment decisions among university students in Surabaya. This study employs a quantitative approach, using a probability sampling technique with a total of 98 respondents. The type of data used in this research is primary data. Data analysis was conducted using Partial Least Squares (PLS) with the SmartPLS software. The results indicate that overconfidence, risk tolerance, and herding behavior have a positive and significant effect on cryptocurrency investment decisions. These findings support behavioral finance theory, which asserts that psychological and social factors influence investment decisions. This study is expected to contribute to the improvement of financial literacy among students and serve as a consideration for novice investors in making more informed investment decisions.